Polarity-Specific Cortical Effects of Transcranial Direct Current Stimulation in Primary Somatosensory Cortex of Healthy Humans - Rehmann, Robert; Sczesny-Kaiser, Matthias; Lenz, Melanie; Gucia, Tomasz; Schliesing, Annika; Schwenkreis, Peter; Tegenthoff, Martin; Höffken, Oliver (Frontiers in Human Neuroscience, 2016)
Transcranial direct current stimulation (tDCS) is a noninvasive stimulation method that has been shown to modulate the excitability of the motor and visual cortices in human subjects in a polarity dependent manner in previous studies. The aim of our study was to investigate whether anodal and cathodal tDCS can also be used to modulate the excitability of the human primary somatosensory cortex (S1). We measured paired-pulse suppression (PPS) of somatosensory evoked potentials in 36 right-handed volunteers before and after anodal, cathodal or sham stimulation over the right non-dominant S1. Paired-pulse stimulation of the median nerve was performed at the dominant and non-dominant hand. After anodal tDCS, PPS was reduced in the ipsilateral S1 compared to sham stimulation, indicating an excitatory effect of anodal tDCS. In contrast, PPS in the stimulated left hemisphere was increased after cathodal tDCS, indicating an inhibitory effect of cathodal tDCS. Sham stimulation induced no pre-post differences. Thus, tDCS can be used to modulate the excitability of S1 in polarity-dependent manner, which can be assessed by paired-pulse suppression. An interesting topic for further studies could be the investigation of direct correlations between sensory changes and excitability changes induced by tDCS.